Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Volume 8A: 45th Mechanisms and Robotics Conference (MR) 2021
DOI: 10.1115/detc2021-69203
|View full text |Cite
|
Sign up to set email alerts
|

Myoelectric Control of Robotic Leg Prostheses and Exoskeletons: A Review

Abstract: Myoelectric signals from the human motor control system can improve the real-time control and neural-machine interface of robotic leg prostheses and exoskeletons for different locomotor activities (e.g., walking, sitting down, stair ascent, and non-rhythmic movements). Here we review the latest advances in myoelectric control designs and propose future directions for research and innovation. We review the different wearable sensor technologies, actuators, signal processing, and pattern recognition algorithms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…One solution to mitigate the vibration in the initial experience is using a lower desired strength for the robot controller in the first moments of using the robot and then increasing it after a while. This approach, i.e., changing the strength from less (initial experience) to high amount (long-term), has been experimentally evaluated in the literature [ 2 , 65 , 66 ], and the results have reported that the method of increasing the strength over time is preferred for human adaptation to robots. Many wearable biomechatronic device users have preferred to initiate with lower controller strength [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One solution to mitigate the vibration in the initial experience is using a lower desired strength for the robot controller in the first moments of using the robot and then increasing it after a while. This approach, i.e., changing the strength from less (initial experience) to high amount (long-term), has been experimentally evaluated in the literature [ 2 , 65 , 66 ], and the results have reported that the method of increasing the strength over time is preferred for human adaptation to robots. Many wearable biomechatronic device users have preferred to initiate with lower controller strength [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have commonly used the proportional gain method [ 2 , 24 , 25 ] ( Figure 2 A). The desired robot torque is calculated as a proportion of the estimated human joint torque (Equation ( 1 )).…”
Section: Mid-level Controllermentioning
confidence: 99%
See 3 more Smart Citations